1979
DOI: 10.1152/ajpheart.1979.236.1.h53
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic conductivity of the endothelial and outer layers of the rabbit aorta

Abstract: Pressure-driven fluid flow across the arterial wall was measured to determine wall hydraulic conductivity (Lp) before and after removal of the endothelium. The thoracic aortas of rabbits, anesthetized with Nembutal, were cannulated, perfused with oxygenated Ringer solution, and removed. With one cannula connected to a capillary manometer and the other closed, the manometer meniscus shift could be used as an indication of fluid loss through the wall plus vessel volume increase (creep). The latter effect, when m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 0 publications
1
24
1
Order By: Relevance
“…The remaining unknown in Eq. 36 is Darcy's permeability of the arterial wall, and it is estimated to be K p ϭ 1.2 ϫ 10 Ϫ18 m 2 , which agrees well with the literature values of 1.0 Ϫ 2.0 ϫ 10 Ϫ18 m 2 (10,25,31,34,39). Once the permeability of the wall is fixed, the last remaining unknown, L p,nj, is estimated with Eq.…”
Section: H911 Mass Transport Of Ldl With Effects Of Wall Shear Stresssupporting
confidence: 82%
“…The remaining unknown in Eq. 36 is Darcy's permeability of the arterial wall, and it is estimated to be K p ϭ 1.2 ϫ 10 Ϫ18 m 2 , which agrees well with the literature values of 1.0 Ϫ 2.0 ϫ 10 Ϫ18 m 2 (10,25,31,34,39). Once the permeability of the wall is fixed, the last remaining unknown, L p,nj, is estimated with Eq.…”
Section: H911 Mass Transport Of Ldl With Effects Of Wall Shear Stresssupporting
confidence: 82%
“…Ϫ8 cm·s Ϫ1 ·mmHg Ϫ1 at 180 mmHg, slightly lower than our value since the SI may be (only) slightly more compressed(24) at the higher ⌬P*. Using a more primitive measurement technique, Vargas et al (65) found 11.9 ϫ 10 Ϫ8 cm·s Ϫ1 ·mmHg Ϫ1 at 74 mmHg, higher than our value but closer to Tedgui and Lever's 70 mmHg value. At 70 mmHg, the SI is much less compressed, leading to a higher apparent endothelial L p * , than at 100 mmHg (22,24).…”
Section: Parameterscontrasting
confidence: 59%
“…Vargas et al (42) maintained the rabbit aorta's cylindrical shape and used a weighing method to measure the transmural flow rate. Tedgui and Lever (38) calculated the transmural flow at 70 and 180 mmHg on the same vessel by measuring the velocity of an air bubble in a horizontal catheter connecting the pressurized water source to the rabbit's isolated vessel lumen.…”
mentioning
confidence: 99%